Panel Discussion: Treatment options for relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL) patients (Canadian Hematology Today, 2022)
Approximately 40% of Diffuse large B cell lymphoma (DLBCL) patients relapse or do not respond to first line therapy. Deciding whether to pursue intensive therapies in these patients is complex, given the limited therapeutic access landscape for R/R DLCBL patients, as well as the risk of serious adverse events. Emerging therapies open up new possibilities.